Monocyte Distribution Width: A Novel Indicator of Sepsis-2 and Sepsis-3 in High-Risk Emergency Department Patients*. Issue 8 (August 2019) - Crouser, Elliott D.; Parrillo, Joseph E.; Seymour, Christopher W.; Angus, Derek C.; Bicking, Keri; Esguerra, Vincent G.; Peck-Palmer, Octavia M.; Magari, Robert T.; Julian, Mark W.; Kleven, Jennifer M.; Raj, Paarth J.; Procopio, Gabrielle; et al.
Abstract : Objectives: Most septic patients are initially encountered in the emergency department where sepsis recognition is often delayed, in part due to the lack of effective biomarkers. This study evaluated the diagnostic accuracy of peripheral blood monocyte distribution width alone and in combination with WBC count for early sepsis detection in the emergency department. Design: An Institutional Review Board approved, blinded, observational, prospective cohort study conducted between April 2017 and January 2018. Setting: Subjects were enrolled from emergency departments at three U.S. academic centers. Patients: Adult patients, 18–89 years, with complete blood count performed upon presentation to the emergency department, and who remained hospitalized for at least 12 hours. A total of 2, 212 patients were screened, of whom 2, 158 subjects were enrolled and categorized per Sepsis-2 criteria, such as controls ( n = 1, 088), systemic inflammatory response syndrome ( n = 441), infection ( n = 244), and sepsis ( n = 385), and Sepsis-3 criteria, such as control ( n = 1, 529), infection ( n = 386), and sepsis ( n = 243). Interventions: The primary outcome determined whether an monocyte distribution width of greater than 20.0 U, alone or in combination with WBC, improves early sepsis detection by Sepsis-2 criteria. Secondary endpoints determined monocyte distribution width performance for Sepsis-3 detection. Measurements and Main Results: Monocyte distribution width greater than 20.0 U distinguished sepsis from all other conditions based on either Sepsis-2 criteria (area under the curve, 0.79; 95% CI, 0.76–0.82) or Sepsis-3 criteria (area under the curve, 0.73; 95% CI, 0.69–0.76). The negative predictive values for monocyte distribution width less than or equal to 20 U for Sepsis-2 and Sepsis-3 were 93% and 94%, respectively. Monocyte distribution width greater than 20.0 U combined with an abnormal WBC further improved Sepsis-2 detection (area under the curve, 0.85; 95% CI, 0.83–0.88) and as reflected by likelihood ratio and added value analyses. Normal WBC and monocyte distribution width inferred a six-fold lower sepsis probability. Conclusions: An monocyte distribution width value of greater than 20.0 U is effective for sepsis detection, based on either Sepsis-2 criteria or Sepsis-3 criteria, during the initial emergency department encounter. In tandem with WBC, monocyte distribution width is further predicted to enhance medical decision making during early sepsis management in the emergency department. Abstract : Supplemental Digital Content is available in the text.